Hubungan Dukungan Keluarga Terhadap Kesehatan Lansia Pada Posyandu Lansia Terintegrasi - Natalia, Betsyeba Glory; Kumala, Desi; Yulita, Chrisdianti (Bunda Edu-Midwifery Journal (BEMJ), 2026)
The increasing number of elderly populations requires sustainable community-based health services through Integrated Elderly Posyandu. Family support is considered an important factor influencing elderly health and participation in health services. This study aimed to determine the relationship between family support and elderly health in participating in Integrated Elderly Posyandu at the UPTD Puskesmas Pahandut area, Palangka Raya City. This study used a quantitative method with a cross sectional design. The sample consisted of 47 elderly respondents selected using accidental sampling technique. Data were collected using family support and elderly health questionnaires and analyzed using the Spearman Rank test. The results showed that most respondents had high family support (51.1%) and good health status (57.4%). Statistical analysis indicated a significant relationship between family support and elderly health with a p-value less than 0.001 and a correlation coefficient of 0.695, indicating a strong positive relationship. Family support plays an important role in improving elderly health in participating in Integrated Elderly Posyandu activities.